Molecular Diagnosis and Synergistic Therapeutic Strategies for Pigeon Malaria - Elangovan, Tamileniyan; Murugesan, Jeevitha; Koperumselvan, Karthika; Muthusamy, Veeraselvam; Annamalai, Latchumikanthan; Mani, Saravanan; Rangasamy, Velusamy (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A flock of 12 domestic pigeons were presented to Veterinary Clinical Complex of the Institute at Orathanadu (India) with the history of  complete inappetence, greenish diarrhoea and regurgitation. Clinical examination of the birds showed signs of dullness and soiled vent.  On blood smear examination a characteristic halter shaped gamont of Haemoproteus columbae encircling the nucleated red blood cells  were observed and confirmed molecularly as Haemoproteus sp. with genus-specific primer. The blood picture revealed increased white  blood cells count suggesting acute parasitemia. The flies Pseudolynchia canariensis were recovered from the wings and body surface of  the pigeons. The birds were treated with Chloroquine phosphate @ 5 mg/kg b.wt., orally for six days and two doses of Buparvaquone  @ 5 mg/kg b.wt., i/m at 72 h interval with multivitamin supplementation. After six days of synergistic therapy the clinical condition of  the pigeons showed complete recovery without any complication.
Keywords: Buparvaquone; Chloroquine; Domestic pigeon; Haemoproteus sp; Pigeon malaria